36 Evaluation Identity within Environmental Sustainability Case Study: The Housing of the Pilgrims in Azizia District - Holy Mecca - Mostafa Yossef, أيمن محمد (Journal of King Abdulaziz University: Environmental Design Sciences, 2022)
There is a global trend to assess the cities within sustainability, also, the identity is one of ‎the most important challenges of the urban field here shows the main question of the research is ‎how to assess identity within sustainability? The research aims to develop a sustainability ‎measurement tool for architectural identity through the inductive approach, and examine how it ‎could be applied to the case study of the housing of the pilgrims in Mecca through the ‎analytical descriptive approach, the research has concluded some important theoretical ‎findings such as the development of the concept of identity and that identity can be measured ‎and analyzed through four criteria (character, passive design, renewable energy, building ‎materials, and sustainable use) and each criterion has measurement objectives and indicators, ‎In the case study in the housing of the pilgrims in Holy Mecca, it was reached that all buildings ‎were failed to take into account renewable energy and about 38% were of an international ‎character with a weakly passive design with poorly sustainable construction materials. 5% ‎International character in median passive design with low sustainability building materials, ‎‎13% International character in median passive design with median sustainability building ‎materials, 16% Local and historic in median passive design with median sustainability building ‎materials, 29% Local and historical character in medium building materials with good passive ‎design with medium sustainability building materials. The research recommended that the use ‎and development of an identity assessment tool check the status quo be used as a basis for ‎development policy development and sustainability.